The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13104-017-2515-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin resistant Staphylococcus aureus in Lumbini Medical College and Teaching Hospital, Palpa, Western Nepal

Abstract: BackgroundMultidrug resistant Staphylococcus aureus is common in both tertiary and primary health care settings. Emergence of methicillin resistance in S. aureus (MRSA) along with macrolide, lincosamide, streptogramin B (MLSB) has made treatment of Staphylococcal infection more challenging. The main objective of this study was to detect MRSA, MLSB (inducible; MLSBi and constitutive; MLSBc) resistant S. aureus using phenotypic methods and to determine their antibiogram.MethodsVarious samples were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 15 publications
9
32
2
Order By: Relevance
“…Among bacterial isolates, 1/4th of them were S. aureus. The findings of our study are consistent with other studies reported from School of Health & Allied Sciences, Pokhara University, 22 Chitwan, 16 B&B hospital, Lalitpur, 30 Manipal Teaching Hospital, Pokhara, 31 Lumbini Medical College and Teaching Hospital, Palpa, 20 Alka Hospital, Lalitpur, 23 and Birendra Military Hospital, Kathmandu. 32 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among bacterial isolates, 1/4th of them were S. aureus. The findings of our study are consistent with other studies reported from School of Health & Allied Sciences, Pokhara University, 22 Chitwan, 16 B&B hospital, Lalitpur, 30 Manipal Teaching Hospital, Pokhara, 31 Lumbini Medical College and Teaching Hospital, Palpa, 20 Alka Hospital, Lalitpur, 23 and Birendra Military Hospital, Kathmandu. 32 …”
Section: Discussionsupporting
confidence: 93%
“… 16 - 22 Past studies conducted at different settings in Nepal have shown the prevalence of MRSA ranging from 26.1% to 57.1%. 16 - 18 , 20 , 21 , 23 Increasingly in recent years, more studies have been carried out to explore the prevalence of MRSA infections in Nepal. Nevertheless, all these studies were mostly concentrated in phenotypic characterization with antimicrobial susceptibility test.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports of MRSA from Nepal reported a prevalence of 21.1%-69.1%. 11 , 14 - 16 Our result showed the prevalence of MRSA as 70.64% which is alarmingly high as betalactam group of drugs are extensively used in our settings to treat bacterial infections. But this study is in accordance with data published by WHO in 2014.…”
Section: Discussionmentioning
confidence: 75%
“…21 A significant difference in antibiotic resistance between MRSA and MSSA was observed in case of amikacin, ciprofloxacin, gentamycin and erythromycin which correlated with other studies from Nepal. 11 , 14 - 16 …”
Section: Discussionmentioning
confidence: 99%
“…MRSA once confi ned to hospitals, health care environments and patients frequenting such facilities, now has become a serious problem for communities due to its emergence as a major cause of the community- which results the emergence of novel strains furthering the challenges in the fi ght with AMR (Thapa et al 2020). A number of studies are conducted in Nepal which have estimated the prevalence of MRSA ranging from 26.1% to 57.1% (Ansari et al 2014;Kumari et al 2008;Khanal and Jha 2010;Raut et al 2017;Bhomi et al 2016;Shahi et al 2018;Thapa et al 2020;Kandel et al 2020). Although there seems a large number of studies are based on MRSA but almost all studies are merely relied on the phenotypic detection.…”
Section: Introductionmentioning
confidence: 99%